EFEKTIFITAS PELAYANAN PUBLIK PADA DINAS PERINDUSTRIAN PERDAGANGAN DAN PENANAMAN MODAL PROVINSI GORONTALO - Albert Pede (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study is intended to be a significant input for the lead in developing the apparatus. Iintuk purpose of this research is to know how to the development of personnel resources of government to the public service at the Department of Industry, Trade and Investment Gorontalo Province. The results obtained that the development of personnel resources in order to provide excellent service at the Department of Industry, Trade and Investment Gorontalo Province has been done by the party leadership, but still not optimally. In terms of the factors that influence the development of personnel in providing public services, facilities and infrastructure are still lacking to support the implementation of the tasks of the apparatus, such as buildings and not enough working space, office equipment still lacking or are damaged. Another factor is the ability of personnel to operate the equipment that is still less than the maximum.